THE EFFECT OF MATERIAL CHOICE AND PROCESS PARAMETERS ON THE MECHANICAL STRENGTH OF 3D-PRINTED TRANSTIBIAL PROSTHETIC - Shadi Sabeti; Silvia Ursula Raschke; Johanne Mattie (Canadian Prosthetics & Orthotics Journal, 2018)
INTRODUCTION